1999
DOI: 10.1159/000030367
|View full text |Cite
|
Sign up to set email alerts
|

Paraganglioma of the Urinary Bladder: A Case Report and Review of the Japanese Literature

Abstract: We describe a patient with primary paraganglioma of the urinary bladder associated with typical clinical symptoms. Systolic blood pressure frequently increased to 300 mm Hg immediately after micturition. Levels of urinary vanillylmandelic acid excretion and serum norepinephrine were significantly elevated. The tumor was removed by partial cystectomy. Histological examination of the tumor revealed paraganglioma of the urinary bladder. Compared with a review of 53 similar cases reported in Japan, the distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 5 publications
2
3
0
Order By: Relevance
“…Recently, vanillylmandelic acid is gaining increasing attention due to its potential to diagnose pheochromocytoma 42 and paraganglioma of the bladder. 43 Elevated vanillylmandelic acid in urine of BC patients observed in our study was also consistent with its higher urinary level in patients with paraganglioma of the bladder. 43,44 It was observed that concentration of vanillylmandelic acid returns to normal in 1 year after complete removal of the tumor in paraganglioma patients.…”
Section: ■ Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Recently, vanillylmandelic acid is gaining increasing attention due to its potential to diagnose pheochromocytoma 42 and paraganglioma of the bladder. 43 Elevated vanillylmandelic acid in urine of BC patients observed in our study was also consistent with its higher urinary level in patients with paraganglioma of the bladder. 43,44 It was observed that concentration of vanillylmandelic acid returns to normal in 1 year after complete removal of the tumor in paraganglioma patients.…”
Section: ■ Discussionsupporting
confidence: 89%
“…43 Elevated vanillylmandelic acid in urine of BC patients observed in our study was also consistent with its higher urinary level in patients with paraganglioma of the bladder. 43,44 It was observed that concentration of vanillylmandelic acid returns to normal in 1 year after complete removal of the tumor in paraganglioma patients. 45 In addition, the urinary levels of uridine and pseudouridine, endogenous metabolites for the synthesis of RNA, were found to be higher in BC compared to non-BC urine, reflecting the higher energetic state of the tumor.…”
Section: ■ Discussionsupporting
confidence: 89%
“…14 In the analysis of 53 reports of paraganglioma of the urinary bladder in Japan, only 3 cases (6%) had no hypertension, hematuria, or micturition attacks. 12 Unexpectedly, our patient had none of these symptoms and all the urine tests were within normal range. As paraganglioma is diagnosed incidentally, no preoperative study was carried out to determinine the blood or urinary levels of catecholamines.…”
Section: Discussionmentioning
confidence: 53%
“…In the reports only 40% of the cases were preoperatively diagnosed. 12 In evaluation of the cases with a query on paraganglioma, levels of blood and urinary catecholamines, and their metabolites, ultrasonography, computed tomography scan, and magnetic resonance imaging will be useful in differential diagnosis and in localizing the tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation